Agile Methodology :A Study On The Use Of Agile Methodology In Managing Software Development Projects - Jagriti Singh, Mahesh Chandra Joshi, David Campbell, (European Economic Letters (EEL), 2025)
Agile Project Management has become a critical methodology for project delivery into a rapidly changing environment. This research paper covers the basics of Agile, its core principles, methodologies, and benefits, explores the historical context, compares Agile to traditional management, and covers its impact on the overall project landscape. At the same time, this paper defines a few potential problems that may arise during Agile implementation and suggests potential solutions and ways to alleviate possible negative consequences. The paper covers all the essential aspects of the topic and is not limited to the established Agile frameworks since several others exist, such as SAFe or Lean Startup. The centralized issue behind Agile is the increased efficiency, higher business satisfaction, faster time-to-market, and increased power and adaptability of the workforce. While the future of Agile seems nothing but bright, the landscape is not devoid of challenges. The paper has also highlighted potential problems, such as change resistance, scoping, and unsteadiness in requirements, as well as the need for alternative success metrics. The last topic is the potential influence of the discovered problem/aspect and what can be advised to concentrate on further. Based on the past failures and positive corrections, the teams have the potential for full success.